Optimisation of a wind power site through utilisation of flywheel energy storage technology. (May 2020) - Hutchinson, Andrew; Gladwin, Daniel T.
Abstract: Due to the intermittent nature of power generation within a wind farm, power generation often either exceeds or does not meet the export limits of the site. Excess power generated above the export limit is considered as a breach and can cause fines from the local grid operator. The excess energy above the export limit can be exploited to supplement periods of low generation, smoothing the output of the wind farm and providing a larger total output of the site. Due to their resilience to high cycle rates, flywheels are ideally suited to act as an energy store in this scenario. This paper utilises real world data to simulate a wind farm operating in tandem with a Flywheel Energy Storage System (FESS) and assesses the effectiveness of different storage capacities.